2019
DOI: 10.2147/ndt.s218738
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations Of Personality Traits With The Capacity-Performance Discrepancy Of Functional Outcome In Patients With Schizophrenia</p>

Abstract: ObjectiveFunctional capacity, which indicates one’s ability to perform everyday living tasks, contributes to real-world functional performance in patients with schizophrenia. However, functional capacity is sometimes not comparable with functional performance in clinical settings. We hypothesized that specific personality traits are related to this capacity-performance discrepancy of functional outcome.MethodsThe measures in this study were the UCSD Performance-based Skills Assessment Brief (UPSA-B) for functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Furthermore, it is also associated with other psychiatric symptoms, such as social anxiety, in patients with schizophrenia 41,42 . Because fewer social anxiety symptoms and a lesser personality tendency to behave pessimistically have been shown to facilitate social functioning in patients with schizophrenia, 43,44 the present negative relationship, i.e. fewer subjective difficulties in attributional bias were associated with better social functioning, could be consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, it is also associated with other psychiatric symptoms, such as social anxiety, in patients with schizophrenia 41,42 . Because fewer social anxiety symptoms and a lesser personality tendency to behave pessimistically have been shown to facilitate social functioning in patients with schizophrenia, 43,44 the present negative relationship, i.e. fewer subjective difficulties in attributional bias were associated with better social functioning, could be consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 81%
“… 61 Further, functional capacity may not always be an accurate reflection of functional performance. 62 However, one advantage of this type of measurement is that it is not subject to recall bias. 63 …”
Section: Resultsmentioning
confidence: 99%
“…61 Further, functional capacity may not always be an accurate reflection of functional performance. 62 However, one advantage of this type of measurement is that it is not subject to recall bias. 63 Two articles (covering one study) reported using three different functional outcome measures, which were the Objective Social Outcomes Index, Social Network Schedule and the Time Use Survey.…”
Section: Functional Outcome Assessment Measuresmentioning
confidence: 99%
“…Although, some of the subjects in our practice had their needs met through a small number of sessions that included brief psychological support and various service referrals, the rest of the subjects who had difficulties in multiple domains received CCM for 6 months, at their request. Notably, they showed a significant improvement in function after 6 months; such improvement is usually difficult to achieve in chronic patients (Uchino et al, 2019). To address their functional decline, our CCM included the contents as follows: psychological support including supportive psychotherapy incorporating cognitive-behavioural therapy or Morita therapy approaches (Nakamura, 2016), and psychoeducation on distress reduction and coping behaviour for emotional disturbances, depressed mood and symptoms of neurosis such as social anxiety and panic attacks (Aikawa et al, 2018;Nemoto et al, 2019Nemoto et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%